2016
DOI: 10.1186/s13068-016-0661-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ethanol production from corn cobs and switchgrass following a pyrolysis-based biorefinery approach

Abstract: BackgroundOne of the main obstacles in lignocellulosic ethanol production is the necessity of pretreatment and fractionation of the biomass feedstocks to produce sufficiently pure fermentable carbohydrates. In addition, the by-products (hemicellulose and lignin fraction) are of low value, when compared to dried distillers grains (DDG), the main by-product of corn ethanol. Fast pyrolysis is an alternative thermal conversion technology for processing biomass. It has recently been optimized to produce a stream ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 69 publications
2
22
0
2
Order By: Relevance
“…Maize residues have been converted to more efficient solid fuels through briquetting [132][133][134]. Ethanol has been produced from corn residues by [125,135,136]. Corn stover has also been used to produce saturated and monounsaturated aliphatic methyl ketones in the C 11 to C 15 (diesel) range [137,138].…”
Section: Maizementioning
confidence: 99%
“…Maize residues have been converted to more efficient solid fuels through briquetting [132][133][134]. Ethanol has been produced from corn residues by [125,135,136]. Corn stover has also been used to produce saturated and monounsaturated aliphatic methyl ketones in the C 11 to C 15 (diesel) range [137,138].…”
Section: Maizementioning
confidence: 99%
“…Levoglucosan is a useful starting chemical that can be converted into platform chemicals such as levulinic acid, levulinic esters, and 5-(hydroxymethyl) furfural (Yin et al, 2016). Levoglucosan can also serve as a precursor for bioethanol production through hydrolysis followed by fermentation (Luque et al, 2016). However, high severity pretreatment conditions, including high temperature, long reaction time, and high acid concentration, lead to the decomposition of the biomass matrix through the hydrolysis of cellulose and hemicellulose (Eom et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of ethyl acetate was also pointed out by Lian et al 75 who found ethyl acetate to be the best solvent to extract phenolic compounds in the organic phase, leaving LG and acetic acid in the aqueous phase. The group of Luque et al 82 suggested that hydrolysis of bio-oil, followed by neutralization and extraction with ethyl acetate was the best system to generate glucose and remove the major amounts of inhibitors. Islam et al 83 obtained 8.62 g L −1 of ethanol from detoxified hydrolysate of waste cotton bio-oil.…”
Section: Critical Reviewmentioning
confidence: 99%